Advanced Data Security Mechanism by Using Compaction and Encipherment in a Distinct Perspective - Dr. Hoshiyar Singh Kanyal, Anuj Kumar, Vipin Kumar Pal, Aman Shakya, Anurag Goswami (International Journal of Advanced Science and Technology, 2020)
Our study in the area of compaction and encipherment explored that the science behind making the information or the data more secure and compressed, can be achieved by using both the compaction and encipherment together. Our descriptive analytical study states that if we first encrypt the data by using cipher and then compress it by making redundancy low, we can achieve a state where our data can be more secure and smaller in size as compared to previous practices. Text quality assessment has a major area called Data Compaction where attention is required for which different methodologies are defined. The most important step is to choose the best machine algorithm and a good data compaction tool which exhibits different compaction technologies and methodologies. It is indeed a challenging task to decide the best technique among the range of different data compaction techniques available both online and offline. Therefore, it generates a necessity of selecting the right and effective text compaction method along with an algorithm that can help in exposing the best tool among the available ones. An effectual data compaction algorithm would be one which is less time consuming but grantsbettercompaction ratio as compared to other existing techniques. In this paper, we present an amalgamated approach for data compaction which is a combination of Dynamic Bit Reduction method and Huffman Coding.